Implementasi Game Based Learning pada Pembelajaran Bahasa Inggris - Nindian Puspa Dewi; Indah Listiowarni (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
Games are media that can be used in the learning process to stimulate students in teaching and learning activities in the classroom. The game used is a game that has been adapted to the needs of learning in the classroom called game based learning or educational games. English subjects are difficult to learn by elementary students at SDN Bujur Barat II, so the use of learning media is needed to attract students' interest in learning the subject. In this study, an educational game was made based on the SD English curriculum consisting of writing, reading, listening, and speaking, which was built using the Ionic programming language and the PHP Framework.